Stres Mahasiswa Baru Bimbingan Dan Konseling Islam Yang Masih Tinggal Di Ma’had Al-Jami’ah IAIN Pontianak - Tiara, Tiara; Ariani, Putri; Dila Dayana, Sagita Azzahra; Fazny, Bella Yugi (BKI IAIN Pontianak, 2023)
Abstract: This study aims to determine the form of stress experienced by New Islamic Guidance and Counseling Students who still live at Ma'had Al Jami'ah IAIN Pontianak. The type of research used is case study qualitative research using a descriptive approach to obtain data. Data collection using interview and observation instruments. The subjects of this study were 4 new students of Islamic Guidance and Counseling class of 2022 who still live at Ma'had Al Jami'ah. The results of the study found that there were several factors that caused Islamic Guidance and Counseling students to experience stress, one of which was the factor from the Ma'had environment because, when carrying out an activity they looked less enthusiastic and easily tired in carrying out their respective assignments, this can be seen from the observation results when they participate in activities in the organization, these students seem to be more quiet and only play their cellphones.